Critiquing the regulation of private security in the United Kingdom: views from inside the sector. Issue 4 (2nd October 2017) - Mawby, Rob; Gill, Martin
ABSTRACT: The UK Private Security Industry Act 2001 provided the legal mechanism for the statutory regulation of parts of the private security sector with the explicit aim of reducing criminality in the industry and raising standards. It created the Security Industry Authority as the regulator which commenced operation in 2003. Since then, it has received mixed reviews, and proposals have been forwarded to change its status and the way it works. This paper provides insights from two groups most affected by regulation: security specialists who buy security, and managers and directors of security companies who are subject to regulation and work with its strengths and weaknesses. The paper reports on their views of both the existing regime and some proposed changes. It suggests that the regulator and the industry share similar views albeit there has been a lack of emphasis on what it takes to enhance the ability of the industry to support the public generally rather than just those who pay.